Serum amyloid A primes microglia for ATP-dependent interleukin-1β release - Facci, Laura (J Neuroinflammation, 2018)
BACKGROUND: Acute-phase response is a systemic reaction to environmental/inflammatory insults and involves production of acute-phase proteins, including serum amyloid A (SAA). Interleukin-1β (IL-1β), a master regulator of neuroinflammation produced by activated inflammatory cells of the myeloid lineage, in particular microglia, plays a key role in the pathogenesis of acute and chronic diseases of the peripheral nervous system and CNS. IL-1β release is promoted by ATP acting at the purinergic P2X(7) receptor (P2X(7)R) in cells primed with toll-like receptor (TLR) ligands. METHODS: Purified (> 99%) microglia cultured from neonatal rat cortex and cerebellum were first primed with the putative TLR4/TLR2 agonist SAA (recombinant human Apo-SAA) or the established TLR4 agonist lipopolysaccharide (LPS) followed by addition of ATP. Expression of genes for the NLRP3 inflammasome, IL-1β, tumor necrosis factor-α (TNF-α), and SAA1 was measured by quantitative real-time polymerase chain reaction (q-PCR). Intracellular and extracellular amounts of IL-1β were determined by ELISA. RESULTS: Apo-SAA stimulated, in a time-dependent manner, the expression of NLRP3, IL-1β, and TNF-α in cortical microglia, and produced a concentration-dependent increase in the intracellular content of IL-1β in these cells. A 2-h ‘priming’ of the microglia with Apo-SAA followed by addition of ATP for 1 h, resulting in a robust release of IL-1β into the culture medium, with a concomitant reduction in its intracellular content. The selective P2X(7)R antagonist A740003 blocked ATP-dependent release of IL-1β. Microglia prepared from rat cerebellum displayed similar behaviors. As with LPS, Apo-SAA upregulated SAA1 and TLR2 mRNA, and downregulated that of TLR4. LPS was less efficacious than Apo-SAA, perhaps reflecting an action of the latter at TLR4 and TLR2. The TLR4 antagonist CLI-095 fully blocked the action of LPS, but only partially that of Apo-SAA. Although the TLR2 antagonist CU-CPT22 was inactive against Apo-SAA, it also failed to block the TLR2 agonist Pam(3)CSK(4). CONCLUSIONS: Microglia are central to the inflammatory process and a major source of IL-1β when activated. P2X(7)R-triggered IL-1β maturation and export is thus likely to represent an important contributor to this cytokine pool. Given that SAA is detected in Alzheimer disease and multiple sclerosis brain, together with IL-1β-immunopositive microglia, these findings propose a link between P2X(7)R, SAA, and IL-1β in CNS pathophysiology. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12974-018-1205-6) contains supplementary material, which is available to authorized users.